The nature and measurement of labour turnover - Van der Merwe, Roux (Rhodes University, Faculty of Humanities, Department of Sociology and Social Work, 1970)
From the Introduction, p. 1-2. The main purposes of this study are to examine the methods by which one particular aspect of industrial behaviour, namely that of the worker's final withdrawal from the work situation, can be measured; to offer a more refined technique for the measurement of such withdrawals, and thirdly to attempt to relate this measurable phenomenon of withdrawal, commonly known as Labour Turnover, to the less easily measurable phenomenon of the integration of the individual worker into his working group. Labour Turnover - or the loss, over time, of employees from an employing organisation - is normally regarded as a province of study appropriate to the field of Industrial Psychology, and to its related applied field of Personnel Management. To a large extent, however, (as will be illustrated in Chapter II of this work) the results of such studies have proved inconclusive, and contradictory, and there is little evidence of progress towards a comprehensive understanding of the subject. This is undoubtedly due to the fragmentary nature of most studies in this field. These have generally been limited to the narrow confines of one particular aspect of the phenomenon, and consequently it has not been viewed against a sufficiently broad background.
Keywords: Labor turnover -- South Africa; Industrial relations -- South Africa; Absenteeism (Labor) -- South Africa